COLLOCATION AWARENESS AND ITS RELATIONSHIP TO READING COMPREHENSION ON FIFTH SEMESTER STUDENTS AT UNIVERSITY OF ISLAM MALANG - fikri mutohari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract : This study aimed to find and describe the relationship between students’ collocation knowledge and their reading comprehension. The method used was quantitative method with the correlational study as the research design of study. The population of this study was fifth semester students who enrolled in English Department of Faculty of Teacher Training and Education at University of Islam Malang, and 23 students were chosen using purposive-sampling technique. The instruments used for collecting data were adaptation of collocation awareness and reading comprehension tests. The data obtained were calculated by using Shapiro-Wilk to measure the normality of data and Pearson Product Moment Correlation to find out whether there was any relationship between the two variables. Based on the research analysis, the relationship between the two variables was found the value of correlation coefficient was .348. The value was lower than the value of Correlation coefficient table at the significant of 1%, in which .348 < .549. It can be drawn a conclusion that there is no significant relationship of both variables, collocation awareness and reading comprehension. In the other words, collocation awareness is not the significant aspect to influence reading comprehension on fifth semester students of Faculty of Teacher Training and Education at English Department of University of Islam Malang.Key words: collocation awareness, reading comprehension, correlation